Incremental value of HBcrAg to classify 1582 HBeAg‐negative individuals in chronic infection without liver disease or hepatitis. Issue 6 (19th January 2021) - Brunetto, Maurizia R.; Carey, Ivana; Maasoumy, Benjamin; Marcos‐Fosch, Cristina; Boonstra, André; Caviglia, Gian Paolo; Loglio, Alessandro; Cavallone, Daniela; Scholtes, Caroline; Ricco, Gabriele; Smedile, Antonina; Riveiro‐Barciela, Mar; et al.
Summary: Background: An accurate, single‐point differential diagnosis between HBeAg‐negative infection (ENI) and chronic hepatitis B (CHB) is an unmet need. Aims: To assess the diagnostic value of the new hepatitis B core‐related antigen (HBcrAg) assay. Methods: A retrospective anonymised data analysis was performed in a multicentre European (nine centres and six countries) cohort of 1582 consecutive HBsAg‐positive/HBeAg‐negative subjects classified according to EASL guidelines as: 550‐CHB, 710‐ENI and 322‐GZ (grey‐zone, HBV‐DNA <20 000 IU/mL). Results: Mean age was 44 (±13.2 y), 59% were men; HBV genotypes were 15% A, 2% B, 2% C, 45% D, 9% E, 1% F and 26% unknown. Median HBV‐DNA serum levels were 2.2 (1.5‐2.7), 3.5 (3.2‐3.8) and 5.6 (4.8‐6.6) logIU/mL in ENI, GZ and CHB, P < 0.0001. HBsAg serum levels (HBsAgsl) were comparable in CHB and GZ, but lower in ENI (2.9 [2.1‐3.6] logIU/mL), P < 0.0001. HBcrAg serum levels (HBcrAgsl) were <3 logU/mL in 90.7% (644/710) ENI, 75.2% (242/322) GZ and 4.7% (26/550) CHB ( P < 0.0001). Median HBcrAgsl were 4.8 (3.9‐5.7), 2.5 (2.0‐2.9) and 2.0 (2.0‐2.5) logU/mL in CHB, GZ and ENI, ( P < 0.0001). ROC‐AUCs for HBcrAg and HBsAg were 0.968 (95% CI, 0.958‐0.977) and 0.732 (95% CI, 0.704‐0.760) respectively. The optimal HBcrAgsl cut‐off to distinguish CHB from ENI was 3.14 logU/mL (95% CI, 3.02‐3.25, 91% SE, 93% SP and 92.4% DA). HBcrAgsl were associated with HBV genotypes ( P < 0.001, one‐way ANOVA) but using genotype‐specific cut‐offs, HBcrAg DA remained unchanged with overlapping 95% CI. Conclusion: The HBcrAg assay showed high diagnostic performance in the accurate single‐point identification of patients with HBeAg‐negative CHB, independently of HBV genotype. This should prompt future prospective studies to confirm its diagnostic role in clinical practice. Abstract : HBcrAg a new tool to identify Chronic Hepatitis B. The diagnostic value of Hepatitis B core‐related Antigen (HBcrAg) was assessed in 1582 consecutive untreated HBsAg‐positive/HBeAg‐negative subjects admitted in 9 European Centers. HBcrAg showed a higher diagnostic performance as compared to HBsAg in the identification of Chronic Hepatitis B patients from HBsAg carriers with HBeAg negative infection, independently of HBV genotype with 91% sensitivity, 93% specificity and 92.4% diagnostic accuracy using a threshold of 3.14 U Log/ml. HBcrAg serum levels appear to be a useful new viral marker to improve the clinical management of untreated HBeAg negative carriers enabling an accurate, fast single point identification of patients who need additional evaluation and possibly antiviral treatment. Legend to the figure: HBsAg and HBcrAg serum levels in HBeAg negative Chronic Hepatitis B (Black circles) and HBeAg negative infection (Red circles) .